NADPH Oxidases and Angiotensin II Receptor Signaling - Garrido, Abel Martin (2008)
Over the last decade many studies have demonstrated the importance of reactive oxygen species (ROS) production by NADPH oxidases in angiotensin II (Ang II) signaling, as well as a role for ROS in the development of different diseases in which Ang II is a central component. In this review, we summarize the mechanism of activation of NADPH oxidases by Ang II and describe the molecular targets of ROS in Ang II signaling in the vasculature, kidney and brain. We also discuss the effects of genetic manipulation of NADPH oxidase function on the physiology and pathophysiology of the renin angiotensin system.